If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 10 = 4x + -25 Reorder the terms: 10 + 11x = 4x + -25 Reorder the terms: 10 + 11x = -25 + 4x Solving 10 + 11x = -25 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 10 + 11x + -4x = -25 + 4x + -4x Combine like terms: 11x + -4x = 7x 10 + 7x = -25 + 4x + -4x Combine like terms: 4x + -4x = 0 10 + 7x = -25 + 0 10 + 7x = -25 Add '-10' to each side of the equation. 10 + -10 + 7x = -25 + -10 Combine like terms: 10 + -10 = 0 0 + 7x = -25 + -10 7x = -25 + -10 Combine like terms: -25 + -10 = -35 7x = -35 Divide each side by '7'. x = -5 Simplifying x = -5
| 7v+2w-6v-3w= | | 4cosx*4cosx=0 | | 3.68-(6.72+2)= | | 6(4x-4)=3(8x+8) | | -y+5x=13 | | ln(x^3)=9 | | 2a^2+a+1=0 | | 2a=a+12 | | -28x-4(2x-5)= | | 2(2x+3)=2(x+15) | | 6=n^2+3n-12 | | 3(4x+2)=2y-4 | | 8x-4(2x-5)+2= | | -6(-w+3y-2)= | | (3x-2)(5x+1)(4)= | | 6+3q=15 | | 6=10-2w | | 5a-2b-8b+6a= | | 3-2r=2r | | 8x+14+2x=40-(9x+3) | | 2k-4=4 | | 2k-4= | | -10+7(a+3)=4(a-1)+5 | | f(-5)=0 | | 3x+22=4(x-1)-1 | | 1/7w=11 | | (-5)+(-7)= | | 3.67-(5.73+3)= | | 2(3x-5)=-7 | | 4x+7x=3x+5 | | 12x+8y=-1 | | 11x+7x+19=56 |